2014
DOI: 10.1007/s12630-014-0304-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison between the i-gel™ and the air-Q™ supraglottic airways when used by anesthesiology trainees as conduits for tracheal intubation in children

Abstract: Purpose Supraglottic airways are commonly used as conduits for fibreoptic bronchoscopy (FOB)-guided intubation in pediatric patients. We hypothesized that anesthesiology trainees with limited prior experience with FOB-guided intubation through a supraglottic airway in children would intubate the trachea faster through the air-Q TM supraglottic airway than through the i-gel TM . Methods Ninety-six children aged one month to six years were randomized to receive either the i-gel or air-Q for FOB-guided tracheal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…The full texts of 118 articles were examined in detail. We included 65 articles in this network meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of 118 articles were examined in detail. We included 65 articles in this network meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The trials had a median (range [IQR]) sample size of 60 (27–240 [53–100]). Sevoflurane was administered for anaesthesia induction in 44 studies . There were eight crossover designed studies .…”
Section: Resultsmentioning
confidence: 99%
“…Although the i‐gel has been used successfully as a conduit for fiberoptic intubation in children, it was not designed for this purpose. It has been found to provide better views compared to older devices; however, its long and narrow tube in the smaller sized i‐gels (1, 1.5) made SGA removal more problematic compared to the air‐Q …”
Section: Characteristics Of the Perfect Pediatric Sgamentioning
confidence: 99%
“…17 The air-Q provides better fiberoptic views than other first-generation SGAs 16 ; and several studies have shown that it outperforms various SGAs when used as a conduit for fiberopticguided tracheal intubation in children. 16,18,19 The air-Q has been used successfully to provide adequate ventilation and as a conduit for tracheal intubation in children with anticipated and unanticipated difficult airways. 18,20 In children with difficult airways, the air-Q provided adequate ventilation and allowed passage of a cuffed endotracheal tube using fiberoptic guidance and optical stylets.…”
Section: Air-qmentioning
confidence: 99%